2018
DOI: 10.2478/pjph-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Looking for professional identity of public health workers in Poland

Abstract: Introduction.Public health is a specific field, which deals with an improvement of population health. It is an interdisciplinary and intersectoral activity and requires participation of various workers. All current documents and acts in public health field in Poland emphasize on the performance of specific tasks, but leave aside personal status and competencies. Many aspects were not resolved till now, e.g. which domains should be included in public health workforce, the problem of workforce enumeration: how l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The higher values of MRSA in elderly patients might be due to their weak immune systems, visits or stays in healthcare facilities for the long term, and lower standards of hygiene in particular the male gender. [21] According to our data, the majority of MRSA isolates were from wounds (34.5%) followed by blood (14.6%) and tissue (13.2%) infections. Hence, it was confirmed that the most frequent presentation of MRSA infection was SSTI.…”
Section: Discussionmentioning
confidence: 62%
“…The higher values of MRSA in elderly patients might be due to their weak immune systems, visits or stays in healthcare facilities for the long term, and lower standards of hygiene in particular the male gender. [21] According to our data, the majority of MRSA isolates were from wounds (34.5%) followed by blood (14.6%) and tissue (13.2%) infections. Hence, it was confirmed that the most frequent presentation of MRSA infection was SSTI.…”
Section: Discussionmentioning
confidence: 62%
“…Findings from this study showed that during the 9 years (2015-2023), only 41 health policy programs on eye health were developed by LGUs in Poland. Study carried out among local government workers showed that in poviats there is a lack of uniform structures dealing with health issues, including health policy programs [15]. Limited funding and lack the skills needed to plan health policy programs [15] are considered as important barriers in the implementation of health policy programs by LGUs.…”
Section: Out Of 1568 Health Policy Programs Developed Bymentioning
confidence: 99%
“…Study carried out among local government workers showed that in poviats there is a lack of uniform structures dealing with health issues, including health policy programs [15]. Limited funding and lack the skills needed to plan health policy programs [15] are considered as important barriers in the implementation of health policy programs by LGUs. Out of 41 health policy programs on eye health in Poland, 8 were rejected by ATHATS and could not be implemented due to significant mistakes in the programs (mostly related to the type of intervention, target population calculations, and budget estimates.…”
Section: Out Of 1568 Health Policy Programs Developed Bymentioning
confidence: 99%
See 2 more Smart Citations